A COMPARATIVE STUDY OF VICTIM PROTECTION ON THE DOMESTIC VIOLENCE ACCORDING TO LAW IN INDONESIA AND MALAYSIA: (Regulation No. 23/2004 Considering PKDRT & Domestic Violence Act 521 1994 jo. Domestic Violence Act A1538 2017) - Oktrina, Faiha (UNIB Press, 2023)
The United Nations as a representation of the international community even accommodates regulations related to human rights through International Treaties agreed upon by state parties in the world through the Universal Declaration of Human Rights. Domestic violence is one of the most violence that occurred in many countries, which happens in Indonesia and Malaysia. Any violence between current or past intimate partners, wherever and whenever the abuse happens, is considered domestic violence (breach of human right). Physical, sexual, emotional, and financial abuse are all potential forms of violence. Indonesian law and Malaysian law define domestic violence as any act against a person, especially a woman, that results in physical, sexual, psychological, and/or domestic neglect or suffering including threats to commit acts, coercion, or unlawful deprivation of liberty within the domestic sphere. Research in a positive direction without excluding the elements of harmonization and legal politics that exist within the scope of the Republic of Indonesia and the Federated States of Malaysia in the realm of Domestic Violence entitled “A COMPARATIVE STUDY OF THE DOMESTIC VIOLENCE LAW IN INDONESIA AND MALAYSIA” according to Law No. 23 of 2004 on the Elimination of Domestic Violence and Domestic Violence Act 521 of 1994 jo. Domestic Violence Act A1538 2017. In this research, the researcher uses normative legal research, there are two types of groupings, consisting of primary legal material and secondary legal material.